Gene flow and genetic drift in urban environments. Issue 18 (24th September 2019) - Miles, Lindsay S.; Rivkin, L. Ruth; Johnson, Marc T. J.; Munshi‐South, Jason; Verrelli, Brian C.
Abstract: Evidence is growing that human modification of landscapes has dramatically altered evolutionary processes. In urban population genetic studies, urbanization is typically predicted to act as a barrier that isolates populations of species, leading to increased genetic drift within populations and reduced gene flow between populations. However, urbanization may also facilitate dispersal among populations, leading to higher genetic diversity within, and lower differentiation between, urban populations. We reviewed the literature on nonadaptive urban evolution to evaluate the support for each of these urban fragmentation and facilitation models. In a review of the literature with supporting quantitative analyses of 167 published urban population genetics studies, we found a weak signature of reduced within‐population genetic diversity and no evidence of consistently increased between‐population genetic differentiation associated with urbanization. In addition, we found that urban landscape features act as barriers or conduits to gene flow, depending on the species and city in question. Thus, we speculate that dispersal ability of species and environmental heterogeneity between cities contributes to the variation exhibited in our results. However, >90% of published studies reviewed here showed an association of urbanization with genetic drift or gene flow, highlighting the strong impact of urbanization on nonadaptive evolution. It is clear that species biology and city heterogeneity obscure patterns of genetic drift and gene flow in a quantitative analysis. Thus, we suggest that future research makes comparisons of multiple cities and nonurban habitats, and takes into consideration species' natural history, environmental variation, spatial modelling and marker selection.